Impact of nutrient dynamics on chlorophyll-a concentrations in non-interconnected lakes: A study in the Vellore and Chennai region - Raghul Mageswaran; Porchelvan Ponnusamy (Results in Engineering)
This study examines the physicochemical dynamics and their impact on chlorophyll-a concentrations in six non-interconnected lakes between Vellore and Chennai city. Data were collected every quarterly in 2024, covering key parameters such as pH, temperature, turbidity, total phosphate, total nitrate, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, and chlorophyll-a. An integrated approach was employed, combining physio-chemical and biological analysis, Principal Component Analysis and GIS mapping. This study fills a research gap by focusing on non-interconnected lakes and demonstrates the importance of regional-scale influences. The experimental results show varying water quality conditions with higher chlorophyll-a concentrations during summer, while nutrient concentrations peak in winter and post-monsoon season. Non-interconnected lakes exhibited uniform seasonal patterns in nutrient levels. PCA identified turbidity, total phosphate, and total nitrate as major contributors to chlorophyll-a variability. During summer, PCA explained 40.02 % of the variance, with high loadings for chlorophyll-a (0.892), total phosphate (0.776), total nitrate (0.693), and turbidity (0.582). Similarly, in post-monsoon season, PCA explained 39.12 % of the variance, with high loadings for chlorophyll-a (0.879), total phosphate (0.812), total nitrate (0.732), and turbidity (0.659), highlighting their contribution to eutrophication. Spatial distribution maps for 2024 indicate that sample 1 from each lake showed higher turbidity, chlorophyll-a, total phosphate, and total nitrate, implying these parameters are critical drivers of eutrophication. Among the lakes, Kaveripakkam exhibited the highest values for these parameters, which needs management strategies. This study helps understand how water quality changes over time and across different locations, providing a basis for better-managing nutrients in freshwater ecosystems.